The Influence of Product Quality, Price and Service Quality on Ana Jetkul Refill Water Consumer Satisfaction and Loyalty - Purba, Yesika; Zunaidi, Rizqa Amelia (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2025)
The human need for drinking water is fundamental and requires quality maintenance to avoid health risks. One option to meet this need is through water refilling, a service provided by Ana Jetkul. As a business that has faced increasing competition over the last decade, Ana Jetkul must have a competitive advantage to continue thriving. This research investigates the impact of product quality, price, and service quality on customer satisfaction and loyalty. The structural equation modelling (SEM) method tests the correlation between variables. Samples are selected using purposive or judgment sampling methods involving the participation of 231 respondents. Data is collected by directly distributing questionnaires to Ana Jetkul's customers. The research results indicate that product quality, price, and service quality influence customer satisfaction. Price, product quality, and customer satisfaction influence service quality. However, the customer satisfaction variable only significantly impacts customer loyalty at Ana Jetkul.